Analisa Kelayakan Nasabah Pembiayaan Konsumtif Melalui Sistem Skoring Pada Bank Sumut Syariah Multatuli Medan - Jihan Atiqah Pane; Rahmi Syahriza (ITB AAS INDONESIA Surakarta, 2023)
Consumptive financing is financing that is used to meet consumption needs that will be used up to meet personal needs outside of business. This research was conducted with the aim of determining the eligibility of prospective customers who will use consumer financing products at banking, especially the Islamic North Sumatra bank, the Multatuli Medan sub-branch office by using a scoring system. This research is descriptive qualitative. Qualitative descriptive, namely analyzing various collected data and then understanding and describing the phenomenon that will be thoroughly investigated through data obtained from the field. The collection of research data was obtained from the results of semi-structured interviews and documentation. This study uses two types of data sources, namely primary data (direct interviews) and secondary data (literature books, journals, and other reference sources). Data analysis in this study was obtained through data collection, data reduction, making conclusions and verification. The results of this study prove that customer feasibility analysis at Bank Sumut Syariah KCP Multatuli when applying for consumer financing by filling in the financing application data based on the Bank Sumut digital web.